…so that I could walk in the final procession for the mortal remains of my beloved father, so that if he had turned around, he would have seen that I was by his side The death of Prince Adam Kazimierz Czartoryski through the eyes of his son, Adam Jerzy - Karpińska, Małgorzata (Requiem, 2025)
On the night of March 20, 1823, Prince Adam Kazimierz Czartoryski passed away in Sieniawa. His eldest son, Adam Jerzy, was not present at the moment of death, but he was the only family member to participate in all mourning ceremonies in Sieniawa. However, he did not accompany the funeral procession carrying the deceased’s body to Warsaw. The article presents how the death of Prince Adam Kazimierz was experienced by his son, who recorded his emotions in an intimate diary at the time. These entries reveal immense pain and a sense of loss that accompanied him during the funeral rites. Simultaneously, Adam Jerzy was deeply bitter about his own behavior. He considered leaving the procession a grave transgression against his father. He accused himself of abandoning his father out of laziness, lacking strong moral fortitude, an inability to stand up for his convictions, and succumbing to the influence of others. This note was meant to serve Prince Adam Jerzy Czartoryski as a means of self-improvement.